2019
DOI: 10.1136/bmjopen-2018-022320
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation among adults with heart failure in sub-Saharan Africa — prevalence, incidence and all-cause mortality: a systematic review and meta-analysis protocol

Abstract: IntroductionHeart failure (HF) remains a major non-communicable disease in sub-Saharan Africa (SSA) associated with high rates of readmission, mortality and loss of economic productivity as it affects mostly young and economically active adults. Atrial fibrillation (AFib) is a major determinant of mortality among patients with HF in SSA. Meanwhile, the use of anti-arrhythmic medications in the region remains unacceptably low. This review aims to evaluate the prevalence and incidence of AFib in adult patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Atrial fibrillation (AF) is the commonest cardiac arrhythmia, and a global public health problem associated with high rates of hospitalisation, disability, and complications such as heart failure, cardiomyopathy, and cardio-embolic events like stroke [1][2][3][4]. The incidence and prevalence of AF have been on a rise globally especially in high-income European countries [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the commonest cardiac arrhythmia, and a global public health problem associated with high rates of hospitalisation, disability, and complications such as heart failure, cardiomyopathy, and cardio-embolic events like stroke [1][2][3][4]. The incidence and prevalence of AF have been on a rise globally especially in high-income European countries [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…The short-term mortality rates we observed in Tanzania are much higher than what has been reported in Kenya [4] , and are also much higher than what has been reported outside of SSA: recent studies from the United States, Canada, and Europe reported thirty-day mortality rates between 0 and 15% 36. , [37] , 38. , 39.…”
Section: Discussionmentioning
confidence: 99%
“…By the difference in proportions calculation, a minimum sample size of 331 patients was needed to provide at least 80% power to detect the difference in mortality rates between patients with AF and those without (two-sided test with a 5% level of significance) 18. Our pretest estimation of AF prevalence was 16% 19 20. For the secondary analyses, this sample size was expected to provide at least 10 observations (ie, number of patients with AF or death events) per predictor in the final models to allow good estimates 21 22.…”
Section: Methodsmentioning
confidence: 99%